Using Facebook Groups as an E-learning Platform: A New Form of Collaborative Learning for Algerian University Students - Boufatah , Imen (Journal of Science and Knowledge Horizons, 2025)
The Covid-19 pandemic accelerated the shift to online learning in Algerian universities, exposing both the potential and limitations of officially adopted Learning Management Systems (LMS) like Moodle. This study investigates why university students preferred Facebook groups over university LMS platforms as e-learning tools during the pandemic. Employing an online questionnaire administered to 41 students from three Algerian universities, the research reveals that while 82.5% of students were aware of their university’s LMS, only 17% actively used it compared to 78% who frequently relied on Facebook groups. Facebook’s user-friendly interface, rapid teacher responsiveness (80.48% reported receiving teacher feedback), and facilitation of collaborative learning through shared resources and collective exam preparation (82.92%) made it the preferred platform. In contrast, the university LMS showed low utilization of interactive features such as forums and chatrooms, primarily due to limited accessibility and under-engagement by instructors. The study highlights the urgent need for enhanced training and support to optimize LMS efficacy while recognizing the complementary role of social media in fostering collaborative e-learning